Introduction to Special Thematic Issue, part 2 "Microsaccades: Empirical Research and Methodological Advances“ - Rudolf Groner (Journal of Eye Movement Research)
Microsaccades are at the interface between basic oculomotor phenomena and complex processes of cognitive functioning, and they also have been a challenge for subtle experimentation and adequate statistical analysis.